The Preferred User: How Audio Description could Change Understandings of Australian Television Audiences and Media Technology. Issue 1 (10th July 2018) - Ellis, Katie; Kent, Mike; Locke, Kathryn
Audio description continues to be unavailable on broadcast television in Australia, despite the technological capabilities to provide it and the existence of a federally funded back catalogue or 'secret library' of audio described television content. This paper reveals findings into both the amount of audio described content that has been created but not made available to television audiences, while also reviewing existing innovative platforms for audio description, such as the app BAM-Describe. It contextualises these findings in an overview of the history of audio description in and outside of Australia, highlighting key technological and policy changes. Evoking theories of the preferred user and how this understanding of television audiences addresses disability, we argue that different interpretations of how audio description can be delivered, determined through a process of interpretive flexibility (and continued industry creativity and innovation) may finally shift the stagnating discussions around audio description provision, and thus ultimately change the accessibility of television for the blind and vision impaired.